Changes in composition of flavour precursor amino acid in leaves of tea (Camellia sinensis) during orthodox black tea processing - Tuan, Hoang Quoc; Thinh, Nguyen Duy; Minh Tu, Nguyen Thi (Vietnam Journal of Science and Technology, 2017)
The content of amino acids in tea leaves at different stages of OTD black tea manufacture was measured. Considerable changes of amino acids were observed in all stages but in each stage, total free amino acids was found to be increase  both in withering fermentation stages and was dramatically decrease at frying stages. The results showed that the some of free a-amino acid contents which was defined as flavour precursor like phenylalnine, methionine and isoleucine in tea leaves were significantly increase during withering whereas they was found to be an decreasing trend during fermentation but others a-amino acid contents like alanine, methionine and glycine was found to be trend increase in both stage of processing. The zero-order, first-order and quadratic models were used to explain the a-amino acid included alanine, valine, isoleucine, leucine and phenylalanine changes kinetics during processing and it was observed that the linear, growth, compounds and quadratic model could be used for explaning the changes of flavour compounds during OTD black tea manufature.